The power of internal feedback: exploiting natural comparison processes. Issue 5 (19th July 2021) - Nicol, David
Abstract: Students generate internal feedback by comparing their current knowledge against some reference information. That information might be planned for by teachers – usually as comments on students' performance – although most information is accessed by students themselves during task engagement, from their interactions with others, with resources and from memories of prior performances. Nearly all research on feedback in higher education focuses on comments as the comparison information. Ongoing and natural feedback comparisons with other information sources have been neglected: hence their potential for learning remains unexplored. To unlock the power of internal feedback, teachers need to have students turn some natural comparisons that they are making anyway, into formal and explicit comparisons and help them build the capacity to exploit their own comparison processes. To envision the possibilities, I present a new model of how students generate internal feedback as they self and co-regulate their learning, using information from multiple sources. I also synthesise two bodies of research to show how comparisons with different kinds of information, singly and in combination, can alter the nature and quality of the internal feedback that students generate. This lens of comparison changes everything. It calls for a fundamental shift in feedback practices and research.